Ritual Adat Tanaile sebuah Ekspresi Identitas Suku Wemale Di Negeri Nuduasiwa untuk Merawat Hormoni Sosial - Ufie, Agustinus (Guidance and Counseling Study Program, Pattimura University, 2018)
Various social phenomena that continue to occur in the midst of our lives, is a side effect of modernization which is characterized by the development of science and technology. Modernization on one side is advantageous but on the other hand detrimental. The disadvantage is actually a blow or a threat to the sustainability of various traditions and cultures of the local community. Various efforts must continue to be blamed in order to strengthen the perspectives of society about the culture and tradition, the effort is also undermined in order to maintain the old paradigm that prioritizes togetherness, harmony, silahturahmi, help. Tanaile's customary ritual is an expression of the identity of the local community, amidst the continuing stretch of modernization. The expression of the identity of the local community is evident through the social and moral values of the Tanaile ritual tradition that must be preserved from generation to generation.